2010
DOI: 10.1089/gtmb.2009.0109
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome Instability in Patients with Chronic Renal Failure

Abstract: This study illustrates increased genetic instability in patients with CRF. These results could also be of a great importance in early diagnosis to prognosticate a possible generation of neoplasm in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 45 publications
(45 reference statements)
1
9
0
Order By: Relevance
“…In patients with ESRD, genomic damage has been shown by numerous biomarkers, such as the analysis of sister chromatid exchange and chromosomal aberrations (Cengiz et al, 1988, Lialiaris et al, 2010, MN frequency (Stopper et al, 1999;Sandoval et al, 2010), comet assay in peripheral lymphocytes (Stopper et al, 2001;Kobras et al, 2006;Aykanat et al, 2011), 8-hydroxy 2-deoxyguanosine content in leukocytes (Tarng et al, 2004), and mitochondrial DNA deletions in skeletal muscle tissue and hair follicles (Liu et al, 2001). Our results also confirmed that patients with ESRD exhibit increased levels of genomic damage, as measured by the MN assay.…”
Section: Discussionsupporting
confidence: 82%
“…In patients with ESRD, genomic damage has been shown by numerous biomarkers, such as the analysis of sister chromatid exchange and chromosomal aberrations (Cengiz et al, 1988, Lialiaris et al, 2010, MN frequency (Stopper et al, 1999;Sandoval et al, 2010), comet assay in peripheral lymphocytes (Stopper et al, 2001;Kobras et al, 2006;Aykanat et al, 2011), 8-hydroxy 2-deoxyguanosine content in leukocytes (Tarng et al, 2004), and mitochondrial DNA deletions in skeletal muscle tissue and hair follicles (Liu et al, 2001). Our results also confirmed that patients with ESRD exhibit increased levels of genomic damage, as measured by the MN assay.…”
Section: Discussionsupporting
confidence: 82%
“…The biomarkers used in these studies were micronuclei in peripheral blood lymphocytes (PBL) (7,(25)(26)(27) and BEC (9), chromosome aberrations and sister chromatid exchanges (28,29), and DNA strand breaks (comet assay) (26-28, 30, 31). The only reports regarding children with CKD were our recent studies using the MN and comet assays in PBL of children (15,16).…”
Section: Resultsmentioning
confidence: 99%
“…The method used was the study of Sister Chromatid Exchanges (SCEs). IFO is a powerful and effective drug performing exceptionally in anticancer therapy, on the other hand it induces chromatid fragility and genotoxicity even in healthy tissue cells (Chen et al 2007;Hansen et al 2007;Lialiaris et al 2010a). As previously stated, Mesna can help to avoid haemorrhagic cystitis induced following administration of IFO.…”
Section: Introductionmentioning
confidence: 92%
“…Employing this method, contributes appreciably in testing efficiently and improving chemotherapeutic techniques. The SCEs method is a notably more sensitive method than the one based on chromosomal aberrations, as chromosome damage is more accurate to detect even in low concentrations of the genotoxic factor (Yilmaz et al 2009, Lialiaris et al 2009a, Lialiaris et al 2010b, Mamur et al 2012, Istifli and Topakt 2012. With respect to the other two cytogenetic markers used, namely PRI and MI, they are both valuable markers of the cytostatic and cytotoxic action of various factors, including the chemotherapeutic ones (Das 1988;Maskaleris et al 1998;Fousteris et al 2006;Lialiaris et al 2009a;Mourelatos et al 2012).…”
Section: Introductionmentioning
confidence: 99%